Leading-effect vs. Risk-taking in Dynamic Tournaments: Evidence from a Real-life Randomized Experiment - Frank Mueller-Langer; Patrick Andreoli-Versbach (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
Two 'order effects' may emerge in dynamic tournaments with information feedback. First, participants adjust effort across stages, which could advantage the leading participant who faces a larger 'effective prize' after an initial victory (leading-effect). Second, participants lagging behind may increase risk at the final stage as they have 'nothing to lose' (risk-taking). We use a randomized natural experiment in professional two-game soccer tournaments where the treatment (order of a stage-specific advantage) and team characteristics, e.g. ability, are independent. We develop an identification strategy to test for leading-effects controlling for risk-taking. We find no evidence of leading-effects and negligible risk-taking effects.
urn:nbn:de:bvb:19-epub-15452-0
Keywords: C93; C21; D01; L83; 330; Tournaments; order effects; leading-effect; risk-taking; randomized natural experiments